Development and characterisation of injection moulded, all-polypropylene composites - A. Kmetty; T. Tabi; J. G. Kovacs; T. Barany (eXPRESS Polymer Letters, 2013)
In this work, all-polypropylene composites (all-PP composites) were manufactured by injection moulding. Prior to injection moulding, pre-impregnated pellets were prepared by a three-step process (filament winding, compression moulding and pelletizing). A highly oriented polypropylene multifilament was used as the reinforcement material, and a random polypropylene copolymer (with ethylene) was used as the matrix material. Plaque specimens were injection moulded from the pellets with either a film gate or a fan gate. The compression moulded sheets and injection moulding plaques were characterised by shrinkage tests, static tensile tests, dynamic mechanical analysis and falling weight impact tests; the fibre distribution and fibre/matrix adhesion were analysed with light microscopy and scanning electron microscopy. The results showed that with increasing fibre content, both the yield stress and the perforation energy significantly increased. Of the two types of gates used, the fan gate caused the mechanical properties of the plaque specimens to become more homogeneous (i.e., the differences in behaviour parallel and perpendicular to the flow direction became negligible).